Cambodia : 2012 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
Despite the global slowdown, Cambodia's economy has been holding up, driven by resilient exports and tourism and a strong real estate recovery. Fiscal policy has remained anchored in rebuilding government deposits and maintaining long-term fiscal debt sustainability, while providing adequate financing for Cambodia's vast development needs. Executive Directors identified greater mobilization of fiscal revenues imperative to rebuild government deposits, and maintained that focus should be on measures that would generate substantial additional revenue and create strong positive externalities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet